1973
DOI: 10.1111/j.1399-3054.1973.tb04830.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Changes in Endogenous Hormone Levels and Shoot Growth Induced by Short Heat Treatments to the Root

Abstract: Heat treatments of two minutes at 46 to 47°C to root systems of Nicotiana rustica and Phaseolus vulgaris affected roots and shoots. Xylem exudate of Phaseolus was collected, and it was found that heat treatment reduced cytokinin levels and increased abscisic acid levels in the exudate. Shoot and root growth of both species was reduced. Root membrane integrity of Nicotiana was measured and was found to be impaired. It is suggested that the changes in hormone activity due to heat treatment regulate the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 14 publications
(14 reference statements)
0
39
0
Order By: Relevance
“…This suggests that high ABA production in roots conducted by xylem flow is related to a reduction in the diffusive conductance of leaves under high soil temperature conditions. A high root temperature reduced the level of cytokinins and increased the level of ABA in the xylem exudate in beans (Itai et al, 1973). In addition, increased levels of ABA and decreased levels of cytokinins in shoots were observed when shoot growth was retarded at high soil temperatures in grass (Liu and Huang, 2005).…”
Section: Photosynthetic Rate Non-structural Carbohydratementioning
confidence: 89%
“…This suggests that high ABA production in roots conducted by xylem flow is related to a reduction in the diffusive conductance of leaves under high soil temperature conditions. A high root temperature reduced the level of cytokinins and increased the level of ABA in the xylem exudate in beans (Itai et al, 1973). In addition, increased levels of ABA and decreased levels of cytokinins in shoots were observed when shoot growth was retarded at high soil temperatures in grass (Liu and Huang, 2005).…”
Section: Photosynthetic Rate Non-structural Carbohydratementioning
confidence: 89%
“…High soil temperature has been found to infl uence the growth and senescence of shoots of different plant species more strongly than shoot temperature (Kuroyanagi and Paulsen, 1988;Udomprasert et al, 1995;Xu and Huang, 2000a). High soil temperature reportedly reduces the cytokinin supply from the root and signals the transportation of abscisic acid from the root to the shoot (Itai et al, 1973;Zhang et al, 1987;Kuroyanagi and Paulsen, 1988;Udomprasert et al, 1995). Roots also play more important role than shoot in regulating the responses of carbohydrate metabolism to heat stress (Xu and Huang, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Wightman (25) reported that, when wheat plants were subjected to decreasing diurnal temperature conditions over a 5-week period, ABA levels were increased to 3-and 10-fold, depending on the variety. Itai et al (10) presented evidence that heat treatment increased the ABA levels in the xylem exudate of bean plants. In that experiment, ABA levels were higher 24 h after the plants had been "topped" and their roots dipped for 2 min in deionized H20 of different temperatures.…”
Section: Resultsmentioning
confidence: 99%